The determinants of reserves disclosure in the extractive industries: evidence from Australian firms - Taylor, Grantley; Richardson, Grant; Tower, Greg; Hancock, Phil (Wiley-Blackwell Publishing Asia, 2012)
This paper examines the determinants of reserves disclosure (RD) in the Australian extractive industries, Our regression results indicate that RD are positively associated with variables relating to corporate governance, foreign listing, existence of reserves in foreign jurisdictions, pledging of reserves in debt covenants, leverage and external (Big 4) auditor, after controlling for firm size, subindustry,shareholder concentration and development/production stage, Additional regression testing shows that the existence of reserves in foreign jurisdictions is the most important determinant of RD in Australia, This paper contributes to a better understanding of the extent and rationale behind the RD practices of Australian resource firms.